Gambaran Gizi Buruk Pada Balita Di Kabupaten Banjarnegara - Evy Rahmadhani; Atika Nur Azizah (2021)
Nutritional problems are actually not a problem caused by poverty alone. Socio-cultural aspects in this case are beliefs, education, and jobs that exist in the community are also other contributing factors. This results in actions that do not support the achievement of adequate nutrition for toddlers. In addition, the socio-economic conditions of a family greatly affect whether or not the needs and affection that will be obtained by children will be fulfilled. This is certainly closely related to family income and parental education. Malnutrition in toddlers has a negative impact on physical and mental growth, which in turn will hinder learning achievement. Objective This study aims to find out the description of malnutrition in children under five in Banjarnegara Regency in 2021. Methods This research uses an observation method with a descriptive approach. The population in this study were infants aged 0 – 59 weeks, as many as 33 toddlers in Banjarnegara Regency, Central Java. Results: Malnutrition in Banyumas Regency based on mother's education level and income, mostly the average level of mother's education is low (Not graduated from elementary school, graduated from elementary school, graduated from junior high school) there are 26 (78.8%) and based on parental income the average -the average income is less than the minimum wage in Banjarnegara Regency Rp. 1,805,000 (66.7%). Conclusion Malnutrition in Banyumas Regency is based on the low level of maternal education and less parental income.